2023
DOI: 10.1097/rlu.0000000000004637
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Malignant Thyroid Nodules Using 18F-FDG PET/CT–Based Radiomics Features in Thyroid Incidentalomas

Abstract: ObjectiveThe purpose of the current study was to evaluate the diagnostic performances of 18F-FDG PET/CT–based radiomics features for prediction of malignant thyroid nodules (TNs) in thyroid incidentaloma (TI).MethodsPubMed, Cochrane database, and EMBASE database, from the earliest available date of indexing through December 31, 2022, were searched for studies evaluating diagnostic performance of 18F-FDG PET/CT–based radiomics features for prediction of malignant TNs in TI. We determined the sensitivities and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Ko et al [36] performed a meta-analysis to investigate the potential of radiomics for the prediction of malignant thyroid nodules in patients with thyroid incidentaloma across 5 studies with 518 patients and found a pooled sensitivity of FDG PET/CT of 0.77 and a pooled specificity of 0.67. The authors concluded that FDG PET/CT-based radiomics features demonstrated a good diagnostic performance for the prediction of malignant thyroid nodules.…”
Section: Classification and Prediction Of Thyroid Nodulesmentioning
confidence: 99%
“…Ko et al [36] performed a meta-analysis to investigate the potential of radiomics for the prediction of malignant thyroid nodules in patients with thyroid incidentaloma across 5 studies with 518 patients and found a pooled sensitivity of FDG PET/CT of 0.77 and a pooled specificity of 0.67. The authors concluded that FDG PET/CT-based radiomics features demonstrated a good diagnostic performance for the prediction of malignant thyroid nodules.…”
Section: Classification and Prediction Of Thyroid Nodulesmentioning
confidence: 99%
“…In the recent meta-analysis by Ko and colleagues 78 , the use of 18 F-FDG PET/CT-based RFs applied to thyroid incidentaloma was investigated. The authors included 5 studies, with differences in terms of RFs extraction and selection methods, types and number of features, and modelling methods.…”
Section: Other Biomarkers For Itn Risk Assessment: Pet/ct Imaging And...mentioning
confidence: 99%
“…CT imaging features from peritumor tissue including shape and texture features were used to predict distance metastasis in locally advanced NSCLC (Dou et al 2018). Recent studies extracted and evaluated radiomic features to predict the clinical prognosis of patients (van Timmeren et al 2017, Ko and Kim 2023).…”
Section: Introductionmentioning
confidence: 99%